Mar, a MITE family of hAT transposons in Drosophila - Deprá, Maríndia (2015)
Background: Miniature inverted-repeat transposable elements (MITEs) are short, nonautonomous DNA elements flanked by subterminal or terminal inverted repeats (TIRs) with no coding capacity. MITEs were originally recognized as important components of plant genomes, where they can attain extremely high copy numbers, and are also found in several animal genomes, including mosquitoes, fish and humans. So far, few MITEs have been described in Drosophila. Results: Herein we describe the distribution and evolution of Mar, a MITE family of hAT transposons, in Drosophilidae species. In silico searches and PCR screening showed that Mar distribution is restricted to the willistoni subgroup of the Drosophila species, and a phylogenetic analysis of Mar indicates that this element may have originated prior to the diversification of these species. Most of the Mar copies in D. willistoni present conserved target site duplications and TIRs, indicating recent mobilization of these sequences. We also identified relic copies of potentially full-length Mar transposon in D. tropicalis and D. willistoni. The phylogenetic relationship among transposases from the putative full-length Mar and other hAT superfamily elements revealed that Mar is placed into the recently determined Buster group of hAT transposons. Conclusion: On the basis of the obtained data, we can suggest that the origin of these Mar MITEs occurred before the subgroup willistoni speciation, which started about 5.7 Mya. The Mar relic transposase existence indicates that these MITEs originated by internal deletions and suggests that the full-length transposon was recently functional in D. willistoni, promoting Mar MITEs mobilization.